STATUS KEWARGANEGARAAN GANDA DI INDONESIA - Femmie Cynthia (Fakultas Hukum Universitas Tarumanagara, 2021)
Citizenship status is a right for everyone, it is stated in Article 28D Paragraph 4 of the 1945 Constitution which states that